Non-invasive diagnosis of infarct artery patency after acute myocardial infarction by use of serial plasma troponin T concentrations: importance of measurement of peak levels. Issue 5 (May 1996) - Norris, R. M.; Johnson, R. N.; White, H. D.; Robinson, D. R.
Abstract : OBJECTIVE: To confirm the validity of a previously described method for assessment of infarct artery patency involving serial measurements of creatine kinase activity by use of troponin T concentration as an independent plasma marker. DESIGN: Streptokinase (1.5 x 10(6) units) was given intravenously to 60 patients within 6 h of onset of prolonged chest pain and ST segment elevation, and blood was taken for measurement of troponin T concentration at baseline and at 1, 2, 3, 4, 8, 12, 16, 20, and 24 h after starting treatment. Coronary arteriography was performed at 2.6 (SD 0.3) h. Plasma troponin T concentration was assessed by two methods: (1) as the absolute rise between 0 and 3 h; and (2) as the proportion of the total rise (from baseline to peak) over the same period. Accuracy for prediction of infarct artery patency, assessed by receiver operating characteristic curves, was compared for both methods of assessment using troponin T and was in turn compared with previously reported results on the same patients using serial measurements of creatine kinase activity. RESULTS: Sufficient values for prediction of patency using troponin T were available in 53 patients. A rise in troponin T between 0 and 3 h to > or = 9% of peak concentration predicted angiographic patency with sensitivity of 94% and specificity of 100%. By contrast, at the optimum cutoff for absolute rate of rise (0.5 micrograms/l/h) sensitivity was only 66% and specificity 86%. Comparable figures for creatine kinase were 92% and 91% (> or = 20% of peak by 3 h) and 62% and 78% (150 IU/l/h). Receiver operating curves confirmed better predictive accuracy for proportions over absolute rates of rise for both markers (P < 0.01). CONCLUSIONS: For accurate diagnosis of infarct artery patency using plasma markers it is necessary to express the rate of rise as a proportion of the peak level. Analysed in this way, both creatine kinase and troponin T are suitable for use in randomised trials of new thrombolytic or adjuvant drugs.